Evaluasi Kinerja Simpang Tak Bersinyal : (Studi Kasus : Simpang 4 tak Bersinyal JL. Raya Seturan - Jl. Selokan Mataram - Jl. Raya Kledokan, Depok, Sleman, Yogyakarta) - Aan Satyawan (FTS 15 UMY 003, 2015)
*3